1989
DOI: 10.1177/002076408903500202
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Parasuicide Repeaters in Kuwait

Abstract: A one-year cohort of 92 parasuicides was followed up at 6 monthly intervals for a period of 2 years since their index parasuicide to study the outcome and evaluate the level of social readjustment. One male patient died of suicide (1.1%) and 18 (19.6%) individuals repeated parasuicide using self-poisoning. The rate of repeated parasuicidal behaviour in this investigation was considerably higher than that reported in comparable studies from developing countries but similar to that from a number of western Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Current work or school problems had a medium-sized protective effect against repetition in four high-/medium quality studies with odds ratios from 0.52 to 0.74. Three lower quality studies [35][37] reported non-significant effects in both directions. Relationship problems had a moderate protective effect against repetition if the relationship in question was one with a partner (ORs: 0.53 to 0.64), friends (ORs: 0.66 to 0.90), or others (ORs: 0.64 to 0.90) but reporting problems with family relationships conferred a slightly increased risk of repetition (ORs: 1.02 to 2.91).…”
Section: Resultsmentioning
confidence: 99%
“…Current work or school problems had a medium-sized protective effect against repetition in four high-/medium quality studies with odds ratios from 0.52 to 0.74. Three lower quality studies [35][37] reported non-significant effects in both directions. Relationship problems had a moderate protective effect against repetition if the relationship in question was one with a partner (ORs: 0.53 to 0.64), friends (ORs: 0.66 to 0.90), or others (ORs: 0.64 to 0.90) but reporting problems with family relationships conferred a slightly increased risk of repetition (ORs: 1.02 to 2.91).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors, however, report that being unemployed is significantly associated with repetition (Dirks, 1998;Kreitman & Casey, 1988;Tejedor, Diaz, Castillon et al, 1999). Suleiman, Moussa, and El-Islam (1989) found that the occupational status of housewife was predictive for a subsequent suicide attempt. No specific studies, to our knowledge, focused on financial dependence and repetitive non-fatal suicide attempts.…”
Section: Economical Statusmentioning
confidence: 99%
“…The modal patient was female, aged 16-25 years, with an adjustment disorder, and overdosing (most commonly with Paracetamol). Suleiman et al (1986Suleiman et al ( , 1989) also studied attempted suicides in Kuwait. The modal attempter was female, under the age of 30, using self-poisoning, reacting to family arguments, and a non-Kuwaiti Arab.…”
Section: Kuwaitmentioning
confidence: 99%